Performing the Cold War in the Postcolonial World Theatre, Film, Literature and Things (Taylor & Francis, 2024)
Cultural Cold War, decolonization, postcolonial studies, cultural diplomacy, national theatre
English
Keywords: History; Cultural Cold War, decolonization, postcolonial studies, cultural diplomacy, national theatre